2003
DOI: 10.1029/2003jd003430
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modeling of seasonal drought effects on canopy CO2/H2O exchange in three Mediterranean ecosystems

Abstract: [1] We present a two-criteria inverse modeling approach to analyze the effects of seasonal drought on ecosystem gas exchange at three Mediterranean sites. The three sites include two nearly monospecific Quercus ilex L. forests, one on karstic limestone (Puéchabon), the other on fluvial sand with access to groundwater (Castelporziano), and a typical multispecies shrubland on limestone (Arca di Noè). A canopy gas exchange model Process Pixel Net Ecosystem Exchange (PROXEL NEE ), which contains the Farquhar photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 53 publications
6
123
1
1
Order By: Relevance
“…Nevertheless, consensus views on processing of data from such networks are being developed to (1) provide estimates of the flux components associated with canopy photosynthesis [gross primary production (GPP)] and ecosystem respiration (Reco) (cf. Falge et al, 2001Falge et al, , 2002aReichstein et al, 2005), (2) reveal seasonal changes in CO 2 exchange potentials (Falge et al, 2002b;Reichstein et al, 2002;Gilmanov et al, 2003), and (3) support the derivation of model parameters for use in spatial generalizations of vegetation/atmosphere CO 2 exchange (Reichstein et al, 2003b;Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, consensus views on processing of data from such networks are being developed to (1) provide estimates of the flux components associated with canopy photosynthesis [gross primary production (GPP)] and ecosystem respiration (Reco) (cf. Falge et al, 2001Falge et al, , 2002aReichstein et al, 2005), (2) reveal seasonal changes in CO 2 exchange potentials (Falge et al, 2002b;Reichstein et al, 2002;Gilmanov et al, 2003), and (3) support the derivation of model parameters for use in spatial generalizations of vegetation/atmosphere CO 2 exchange (Reichstein et al, 2003b;Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other commonly used models [Wang et al, 2001;Reichstein et al, 2003;Knorr and Kattge, 2005;Wang et al, 2007], their model explicitly tracked changes in aboveground and soil carbon pools, thus potentially capturing the dynamics of longer-term processes such as forest succession that influence carbon fluxes over decadal to centennial scales. While their predictions for daily to annual net carbon fluxes improved significantly, their optimized model gave rise to unrealistic long-term carbon dynamics with excessive rates of carbon sequestration in vegetation and excessive decomposition of soil carbon stocks.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several studies have used assimilation techniques to incorporate flux tower measurements into models. Wang et al [2001] used three weeks of eddy-flux measurements to estimate photosynthesis and stomatal conductance parameters of a simplified terrestrial biosphere model designed to predict seasonal-to-interannual carbon fluxes, but found that site-specific model parameters were required to match the observations; similarly, Reichstein et al [2003] optimized an ecosystem model using CO 2 and H 2 O fluxes from Mediterranean ecosystems, but also found that site-and season-dependent model parameters were required. It appears that simplified biosphere and ecosystem models may not be able to make reliable predictions for locations and time periods other than those used in the model fitting.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Trudinger et al (2007) showed that how data errors and uncertainties are treated in the optimization criterion will have a significant impact on the retrieved parameters. Studies using EC data in inverse modelling often assume constant error variance (Reichstein et al, 2003;Owen et al, 2007;Wang et al, 2007), use the standard deviation of the model residuals (Sacks et al, 2006;Braswell et al, 2005) or an adhoc fraction of the observations (Knorr and Kattge, 2005). During the last few years approaches for the quantification of random errors of EC data came up, they used paired observations, first spatially separated measurements (Hollinger et al, 2004), but as there are only few appropriately distanced towers available, Hollinger and Richardson (2005) developed a methodology using daily differenced measurements with equivalent environmental conditions that allowed to characterize the univariate distribution for several sites Richardson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%